In vitro root formation and plantlet development in dendrobium orchid - Khatun, MM; Khatun, H; Khanam, D; Al-Amin, Md (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted to investigate the combined effect of different plant growth regulators with and without charcoal supplementation for root formation and plantlet development from protocorm like bodies (PLBS) of orchid. The combination of BAP + NAA, BAP + IAA, BAP + IBA, and IAA + IBA at different concentrations were studied. It revealed that the highest number of roots was obtained from 1.0 mg/L each of IAA + IBA combination (6.667) and the highest root length was recorded from 2.0 mg/L BAP + 1.0 mg/L IBA with charcoal supplementation. The treatment combinations, 1.0 mg/L each of BAP + NAA, BAP + IAA, BAP + IBA, and IAA + IBA were found best for producing more rooted plantlets with charcoal supplementation. It revealed that charcoal enhanced the root formation. Keywords: Orchid; Dendrobium; hybrid; In vitro rooting. DOI: 10.3329/bjar.v35i2.5888 Bangladesh J. Agril. Res. 35(2) : 257-265, June 2010